Effects of the bulk compressibility on rubber isolator’s compressive behaviors - Wenku Shi (Advances in Mechanical Engineering, 2017)
Through combined experimental and finite element analysis, the effect of bulk compressibility on rubber isolators was studied. First, the strain energy functions for rubber materials were studied, and the volumetric term was described by Poisson’s ratio. Second, parameter identification tests of rubber specimens were performed to obtain basic material properties of strain energy functions. It has shown that bulk compressibility has an important effect on the vertical stiffness of rubber isolators. When the value of Poisson’s ratio is 0.499, the results of simulation and experiment are in good agreement. Based on the finite element analysis model, the stress of the rubber isolator was studied and the structure was improved. In addition, Poisson’s ratio could be used to modify the finite element analysis model of rubber isolators and give rise to the accuracy of the simulation result.